The rheological modification of the Daura asphalt in polycarbonate using the microwave technique - Salam Karash; Khalid AL-Memary (College of Education for Pure Sciences, 2020)
This study has included a modulation of the rheological properties of asphalt by a catalyst chemical treatment with polycarbonate, and the microwave technique was used at a power of (360) watt at time intervals. Furthermore, the modulation and treatment were done in the presence of sulfur and polycarbonate. The formed rheological properties of the new asphalt samples were studied which include (permeability, softening point, ductility and penetration index). Those asphalt samples of the new rheological properties could be used in paving field and some other samples could be used as anti-moisture materials. The best asphalt samples with new rheological properties and those conformable with the properties of roads authority and Iraqi bridges were tested as a tiled asphalt since they were studied in terms of conducting Marshall tests and comparing them with the original sample in order to show the possibility of using the modified samples in the tiling and the obtained results were excellent in terms of stable creeping values. In addition the aging test was applied on the samples that contain good rheological properties. Moreover, the modified asphalt has shown higher dissociation values in comparison with the original asphalt, so the modified asphalt has more resistant to high temperature and acid rains and shows an important characteristic of the quality of the asphalt that enables the modified asphalt to stick more closely to the aggregate, which gives higher resistance and greater operating age life to the streets.